Exogenous applications of salicylic acid alleviate the damaging effects of heat stress in chili (Capsicum frutescens L.) through improved antioxidant defense system - Saeed, Fozia; Rasul, Sumaira; Batool, Sidra; Zafar, Zafar Ullah; Manzoor, Hamid (International Journal of Applied and Experimental Biology, 2023)
Due to global climate change, heat stress is a critical environmental factor for adversely affecting plant growth and productivity. It induces changes in cellular machinery and antioxidant enzymes’ functions in plants. The role of phytohormones especially salicylic acid (SA) is well documented to alleviate the heat stress-induced adverse effects in plants. Here, we investigated the ameliorative role of SA in heat-stressed chili (Capsicum frutescens L.) plants. For this purpose, four-week-old chili plants of three local cultivars (Moro, Tilhari and Ren-02) pretreated with 1 mM and 2 mM SA were subjected to heat stress (42 oC) for 72 h. Our results revealed that heat stress significantly reduced plant height, shoot biomass, chlorophyll contents and relative water contents, while it increased membrane peroxidation and hydrogen peroxide in all three chili cultivars. However, foliar spray with both concentrations of SA (particularly 2 mM) showed prominent recovery effects in high temperature exposed chili cultivars (Moro and Ren-02) with significantly improved biomass production, photosynthetic pigments, relative water contents, and catalase and peroxidase activities compared to their respective controls. Moreover, the foliar spray of 2 mM SA significantly reduced hydrogen peroxide and malonaldehyde contents under the heat stress conditions. In conclusion, SA significantly improved heat tolerance of chili plants by decreasing oxidative stress via increasing antioxidant activity and membrane stability.